Dynamics of Islam in the modern world essays in honor of Jamal Malik - Zarrabi-Zadeh, Saeed; Omerika, Armina 1976-; Gugler, Thomas K. ca. letztes Drittel des 20. Jh; Asbury, Michael E.; Gugler, Thomas K. ca. letztes Drittel des 20. Jh (Brill, 2022)
"Dynamics of Islam in the Modern World scrutinizes and analyzes Islam in context. It posits Muslims not as independent and autonomous, but as relational and interactive agents of change and continuity who interplay with Islamic(ate) sources of self and society as well as with resources from other traditions. Representing multiple disciplinary approaches, the contributors to this volume discuss a broad range of issues, such as secularization, colonialism, globalization, radicalism, human rights, migration, hermeneutics, mysticism, religious normativity and pluralism, while paying special attention to three geographical settings of South Asia, the Middle East and Euro-America"--
Keywords: Geschichte; Islam; Festschrift; Aufsatzsammlung